Dietary patterns and hip fracture in the Adventist Health Study 2: combined vitamin D and calcium supplementation mitigate increased hip fracture risk among vegans - Thorpe, Donna L; Beeson, W Lawrence; Knutsen, Raymond; Fraser, Gary E; Knutsen, Synnove F (The American journal of clinical nutrition, 2021)
Concerns regarding the adequacy of vegetarian diets with respect to fracture risk continue. We aimed to explore the influence of 5 previously defined dietary patterns on hip fracture risk and whether this association is modified by concomitant calcium and vitamin D supplementation. The Adventist Health Study 2 is a prospective cohort study in which participants were enrolled during 2002–2007; proportional hazards regression analyses were used to estimate fracture risk. Participants reside throughout the United States and Canada. A total of 34,542 non-Hispanic white peri- and postmenopausal women and men 45 y and older responded to the biennial hospital history form and were followed for a median of 8.4 y. The study identified 679 incident hip fractures during 249,186 person-years of follow-up. Fracture risk varied according to dietary pattern, with a clear effect modification by concurrent supplementation with both vitamin D and calcium. In multivariable models, including adjustment for calcium and vitamin D supplementation, female vegans had 55% higher risk of hip fracture (HR: 1.55; 95% CI: 1.06, 2.26) than nonvegetarians (NVEGs), whereas there was no association between diet pattern and hip fracture risk in men. When further stratifying females on supplement use with both vitamin D and calcium, vegans taking both supplements were at no greater risk of hip fracture than the subjects with other dietary patterns including the NVEGs. Without combined supplementation of both vitamin D and calcium, female vegans are at high risk of hip fracture. However, with supplementation the excessive risk associated with vegans disappeared. Further research is needed to confirm the adequacy of a vegan diet supplemented with calcium and vitamin D with respect to risk of fracture. Vegans are at increased for hip fractures: Combined supplementation of vitamin D and calcium may rescue this.